Cardiomyocyte-Targeting Peptide to Deliver Amiodarone - Maliha Zahid; Beth Weber; Ray Yurko; Kazi Islam; Vaishavi Agrawal; Jack Lopuszynski; Hisato Yagi; Guy Salama (MDPI AG, 2023)
Background: Amiodarone is underutilized due to significant off-target toxicities. We hypothesized that targeted delivery to the heart would lead to the lowering of the dose by utilizing a cardiomyocyte-targeting peptide (CTP), a cell-penetrating peptide identified by our prior phage display work. Methods: CTP was synthesized thiolated at the N-terminus, conjugated to amiodarone via Schiff base chemistry, HPLC purified, and confirmed with MALDI/TOF. The stability of the conjugate was assessed using serial HPLCs. Guinea pigs (GP) were injected intraperitoneally daily with vehicle (7 days), amiodarone (7 days; 80 mg/kg), CTP-amiodarone (5 days; 26.3 mg/kg), or CTP (5 days; 17.8 mg/kg), after which the GPs were euthanized, and the hearts were excised and perfused on a Langendorff apparatus with Tyrode's solution and blebbistatin (5 µM) to minimize the contractions. Voltage (RH237) and Ca2+-indicator dye (Rhod-2/AM) were injected, and fluorescence from the epicardium split and was captured by two cameras at 570-595 nm for the cytosolic Ca2+ and 610-750 nm wavelengths for the voltage. Subsequently, the hearts were paced at 250 ms with programmed stimulation to measure the changes in the conduction velocities (CV), action potential duration (APD), and Ca2+ transient durations at 90% recovery (CaTD90). mRNA was extracted from all hearts, and RNA sequencing was performed with results compared to the control hearts. Results: The CTP-amiodarone remained stable for up to 21 days at 37 °C. At ~1/15th of the dose of amiodarone, the CTP-amiodarone decreased the CV in hearts significantly compared to the control GPs (0.92 ± 0.05 vs. 1.00 ± 0.03 ms, p = 0.0007), equivalent to amiodarone alone (0.87 ± 0.08 ms, p = 0.0003). Amiodarone increased the APD (192 ± 5 ms vs. 175 ± 8 ms for vehicle, p = 0.0025), while CTP-amiodarone decreased it significantly (157 ± 16 ms, p = 0.0136), similar to CTP alone (155 ± 13 ms, p = 0.0039). Both amiodarone and CTP-amiodarone significantly decreased the calcium transients compared to the controls. CTP-amiodarone and CTP decreased the CaTD90 to an extent greater than amiodarone alone (p < 0.001). RNA-seq showed that CTP alone increased the expression of DHPR and SERCA2a, while it decreased the expression of the proinflammatory genes, NF-kappa B, TNF-α, IL-1β, and IL-6. Conclusions: Our data suggest that CTP can deliver amiodarone to cardiomyocytes at ~1/15th the total molar dose of the amiodarone needed to produce a comparable slowing of CVs. The ability of CTP to decrease the AP durations and CaTD90 may be related to its increase in the expression of Ca-handling genes, which merits further study.